Local Wisdom Based Learning of the Mandar Tribe to Foster Social Awareness in Elementary School Students - Iqbal Arifin; Dyan Paramitha Darmayanti; Darman Manda (Universitas Sulawesi Barat, 2025)
Character education is a crucial pillar in shaping a generation that is not only intellectually intelligent but also socially sensitive and caring towards others. However, in practice, the instilling of character values in elementary schools is often theoretical and not fully internalized by students in their daily lives. This study aims to explore how learning based on the local wisdom of the Mandar tribe can foster social awareness in elementary school students. The study was conducted in three elementary schools in Polewali Mandar Regency, involving nine informants, consisting of teachers, principals, and students. Data were collected through in-depth interviews and observation of learning activities, and then analyzed thematically. The study's results reveal three key findings. First, Mandar cultural values such as Siwaliparri (mutual cooperation), Metawe (mutual respect), Mepuang (hospitality and empathy), and Metabe (shared responsibility) are applied through contextual learning activities based on student experiences. Second, teachers act as value facilitators, connecting the learning process with social practices and daily role models. Third, the internalization of these cultural values has a tangible impact on students' social awareness, as evidenced by the increase in mutual assistance, politeness, empathy, and responsibility within the school environment. These findings confirm that local wisdom-based learning has the transformative power to naturally foster children's social character. Further studies can be conducted to explore the application of cultural values from other regions as an effort to strengthen character education and the Pancasila Student Profile, which is rooted in the nation's culture.